3D dynamic soil-structure interaction in layered, fluid-saturated, poroelastic half-space. Issue 120 (May 2019) - Han, Bing; Liang, Jianwen; Fu, Jia; Liu, Run
Abstract: Three-dimensional (3D) dynamic soil-structure interaction (SSI) is investigated by a model of a multi-degree-of-freedom (MDOF) system on cylindrical rigid foundation embedded in layered, fluid-saturated, poroelastic half-space using the indirect boundary element method (IBEM). The analysis focuses on the effects of site dynamic characteristics and the pore fluid on the SSI. It is shown that the site dynamic characteristics affect the structural responses significantly; with decreasing soil layer thickness, the fundamental peak frequencies of the structural displacements increase; with increasing bedrock stiffness, the fundamental peak values of the structural displacements and pore pressures increase; however, these effects are not as sensitive as those for two-dimensional (2D) models. The pore fluid also affects the structural displacements significantly, especially for layered half-space; the fundamental peak frequencies of the structural displacements are higher than those of the corresponding 3D dry cases, with a shift of up to 7% in this study; additionally, the effects of pore fluid are clearer and more definite than those for 2D models; the fundamental peak values may be larger or smaller than those for the corresponding 3D dry cases, with a difference of up to 12%. Highlights: 3D dynamic SSI in layered, fluid-saturated, poroelastic half-space. 3D model of a MDOF system on embedded cylindrical rigid foundation. The effects of the site dynamic characteristics and pore fluid on structural responses. Difference between 3D fluid-saturated case and 3D dry case, and the difference between 3D fluid-saturated case and 2D fluid-saturated case.